Challenging Glass 3 - Veer, Fred (IOS Press, 2014)
The material properties of glass and its ongoing technological development offer particular opportunities for daylighting and lighting. Our own approach is to consider the possibility of approaching glass as an opportunity for the reestablishment of experiential light in public realm. Electrical lighting at night is one area where quantity is suppressing the possibilities of presenting subtle qualities of light